Extended affine Lie algebras and their root systems - Azam, Saeid; Berman, Stephen, 1944-; Gao, Yun, 1963-; Pianzola, Arturo, 1955- (Memoirs of the American Mathematical Society ;, 1997)
This work is about extended affine Lie algebras (EALA's) and their root systems. EALA's were introduced by Høegh-Krohn and Torresani under the name irreducible quasi-simple Lie algebras. The major objective is to develop enough theory to provide a firm foundation for further study of EALA's.